A review of attitudes towards the reuse of health data among people in the European Union: The primacy of purpose and the common good - Skovgaard, Lea L. (Health Policy, 2019)
Health data are used for still more purposes, and policies are enacted to facilitate data reuse within the European Union. This literature synthesis explores attitudes among people living in the European Union towards the use of health data for purposes other than treatment. Our findings indicate that while a majority hold positive attitudes towards the use of health data for multiple purposes, the positive attitudes are typically conditional on the expectation that data will be used to further the common good. Concerns evolve around the commercialisation of data, data security and the use of data against the interests of the people providing the data. Studies of these issues are limited geographically as well as in scope. We therefore identify a need for cross-national exploration of attitudes among people living in the European Union to inform future policies in health data governance.